Targeting miR-21 to Overcome P-glycoprotein Drug Efflux in Doxorubicin-Resistant 4T1 Breast Cancer - Kim, Eun Hye; Ryu, Youngri; Choi, Jiwoong; Park, Daeho; Lee, Jong Won; Chi, Sung-Gil; Kim, Sun Hwa; Yang, Yoosoo (The Korean Society for Biomaterials | BioMed Central, 2024)
Acquired resistance to chemotherapy is a major challenge in the treatment of triple-negative breast cancer (TNBC). Despite accumulated evidence showing microRNA-21 (miR-21) as a vital regulator of tumor progression, the role of miR-21 in modulating the multidrug resistance of TNBC remains obscure. In this study, we demonstrate that miR-21 affects chemoresistance in 4T1 TNBC cells in response to doxorubicin (DOX) by regulating the P-glycoprotein (P-gp) drug efflux pump. Overexpression of miR-21 in the 4T1 cells markedly reduced their sensitivity to DOX, impeding DOX-promoted cell death. We employed anti-miR-21 oligonucleotide conjugated with a PD-L1-binding peptide (P21) for targeted delivery to 4T1 tumor cells. The selective down-regulation of miR-21 in 4T1 TNBC led to the reversal of P-gp-mediated DOX resistance by up-regulating phosphatase and tensin homolog (PTEN). Our study highlights that miR-21 is a key regulator of drug efflux pumps in TNBC, and targeting miR-21 could enhance DOX sensitivity, offering a potential therapeutic option for patients with DOX-resistant TNBC.